2017
DOI: 10.1080/14616696.2017.1405058
|View full text |Cite
|
Sign up to set email alerts
|

Non-kin ties as a source of support in Europe: understanding the role of cultural context

Abstract: The 'crowding-out' and the 'decline of the family' hypotheses are the fundamental theoretical notions underlying the literature on cross-country differences in informal support. In this study, we expand upon these notions to develop and test the premise that cultural context shapes European's views about an often overlooked source of support: non-kin. We carefully conceptualise cultural context as individualistic values and familialistic norms. Employing multilevel multinomial models and European Quality of Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Thus our results suggest that not only individual characteristics but also country-level factors shape the opportunities for individuals to create and sustain social networks. For example, “restricted” and “child-based” networks were found in contexts that not only have higher old-age poverty (Megyeri, 2016), but also have higher levels of familialism (Kalmijn & Saraceno, 2008) and lack of generalized trust (Conkova et al, 2018; Letki, 2018). Respondents with high probabilities to have “restricted” and “child-based” networks were more common in Eastern and Southern European countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus our results suggest that not only individual characteristics but also country-level factors shape the opportunities for individuals to create and sustain social networks. For example, “restricted” and “child-based” networks were found in contexts that not only have higher old-age poverty (Megyeri, 2016), but also have higher levels of familialism (Kalmijn & Saraceno, 2008) and lack of generalized trust (Conkova et al, 2018; Letki, 2018). Respondents with high probabilities to have “restricted” and “child-based” networks were more common in Eastern and Southern European countries.…”
Section: Resultsmentioning
confidence: 99%
“…Societies with higher levels of economic development tend to have higher levels of individualism (Inglehart, 1997), which are conducive to engaging in social ties outside the immediate family (Conkova, Fokkema, & Dykstra, 2018). Given that the gross domestic product per capita is higher in Northern and Western European countries than in Southern and Eastern European countries (Eurostat, 2017), we expect a higher likelihood of “diverse” and “friend-focused” networks in the first set of countries than in the second set.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From these perspectives, beluga communities have similarities to human societies where social networks, support structures, cooperation and cultures involve interactions between kin and non-kin 76 , 77 . An analysis of human societies may also be instructive in understanding menopause in beluga whales.…”
Section: Discussionmentioning
confidence: 99%
“…Similar arguments may apply to the evolution of social structure in other cetacean species that form fission-fusion societies and/or are non-matrilineal and where groups comprise both kin and non-kin including bottlenose dolphins 30 , northern bottlenose whales (Hyperoodon ampullatus) 74 and possibly Baird's beaked whale (Berardius bairdii) 75 . www.nature.com/scientificreports/ From these perspectives, beluga communities have similarities to human societies where social networks, support structures, cooperation and cultures involve interactions between kin and non-kin 76,77 . An analysis of human societies may also be instructive in understanding menopause in beluga whales.…”
Section: Type Of Groupmentioning
confidence: 99%
“…This paper considers the support of the same activities and expectation of the same outcomes regardless of macro-and micro factors as highly problematic. Many authors showed that the availability of these activities, their outcomes, and their meaning for older people differ substantially (Conkova, Fokkema, & Dykstra, 2017;Hank, 2011;Lakomý, 2019;Timonen, 2016;Walker, 2009). These differences can be explained by many factors structured in several theories.…”
Section: Introductionmentioning
confidence: 99%